Analisis Manajemen Proyek Sistem Informasi Pengolahan Persediaan Data Obat di Klinik Cirendeu Medika Tangerang - Normah Normah; Siti Nurajizah; Rizqitha Maula; Divika Namastute; Alifia Ramadhanti (Universitas Bina Sarana Informatika, 2024)
Digital transformation in the health sector is starting to be intensively implemented. The provision of an integrated health information system is being planned to improve health governance. However, at the Cirendeu Medika Tangerang Clinic, there has not been maximum improvement in this matter, one example is medication recording which is still done manually so it takes a long time and is prone to errors. In supporting this digital transformation, the Cirendeu Medika Tangerang Clinic has begun implementing digitalization in carrying out its business processes. Recording of drug supplies, receipt of drugs, and dispensing of drugs will be done by accessing the website so that it can be well documented. Arrangements for these needs can be carried out if they are included in good planning. This planning can be accommodated through the preparation of a planned, integrated Information Systems Project, so that it can produce output that is efficient and on target.